Microwave-assisted hydro-distillation of Annona Muricata: article - Jemon, Jealonovier Sayas; Kadri, Atikah (2017)
Essential oil from natural products contains abundant medicinal and therapeutic values. Annona Muricata itself had proven to have significant antioxidants and anticancer activities. The development of microwave-assisted hydrodistillation (MAHD) as the alternative extraction methods has gain a lot of attention to produce better quality of essential oil over shorter period of time to overcome to increasing demand of essential oil worldwide. The study aimed to compare the conventional hydro-distillation (HD) and microwave-assisted hydro-distillation (MAHD) to evaluate their effectiveness in the extraction of essential oil from Annona Muricata. The effect of different parameters, such as extraction methods (hydro-distillation and microwave-assisted hydro-distillation) and microwave power on the extraction yield, extraction time and its major chemical compounds were investigated. 100 grams of Annona Muricata leaves were immersed in distilled water and heated by different heating medium, that are heating mantle and microwave oven, using the Clevenger extraction apparatus. The extraction was then carried out under three microwave power levels (100, 300 and 600 W) to determine the best power for higher yield of essential oil. The result found out that MAHD had produced higher yield than HD (0.045%) over shorter period of time (180 minutes). The best microwave power to produce higher yield was found at power level of 600 W with the yield obtained under this condition was 0.045% w/w. Yellowish white essential oil with a strong smell was extracted and the chemical compounds were analyzed using gas chromatography-mass spectrometry (GC-MS). MAHD (600 W) was found to be effective in producing higher yield at shorter extraction time.